Competitive evolved sub‐clonal BCR:ABL1 and novel MSI2:PC fusion genes in myelodysplastic syndrome with isolated del(5q). Issue 1 (1st November 2022) - Zhang, Yanqing; Liu, Yang; Wang, Tong; Wang, Hui; Chen, Xue; Cao, Panxiang; Ma, Xiaoli; Liu, Mingyue; Xu, Ping; Bi, Hailiang; Pan, Jiaqi; Jiang, Yongfang; et al.
Abstract: Myelodysplastic syndrome (MDS) represents a group of neoplasms with extensive heterogeneity. Recurrent mutations in dozens of driver genes have been identified in over 90% of MDS cases, although fusion genes are rarely seen. We first report the competitive evolved sub‐clonal breakpoint cluster region (BCR)::ABL1 and novel MSI2::PC fusion gene in MDS with del(5q) in initial diagnosis that underwent dismal progression. However, the BCR::ABL1 clone vanished while the MSI2::PC clone rose to the major one with disease progression. A novel MSI2::PC fusion transcript was identified in initial diagnosis and disease progression of the patient through transcriptome sequencing (RNA‐seq) and Quantitative reverse transcription polymerase Chain Reaction (PCR) showed MSI2::PC/ABL1 expression at initial diagnosis and disease progression. In addition, mutation screening of 300 leukemia driver genes identified ARID2 c.5046del/p.F1682Lfs*19 and ZNF292 c.4565A > G/p.Q1522R mutation in bone marrow sample at initial diagnosis and disease progression. In conclusion, the dynamic process of the two fusion and phenotype manifestations may help to understand further the molecular significance of the anomalies of BCR::ABL1, MSI2, and PC in oncogenesis.